Dėl baltų substrato Balstogės vaivadijoje (Lenkijoje) - Zinkevičius, Zigmas (Baltistica, 1975)
Concerning the Baltic substratum in Polish in the region of BiałystokThe article presents an analysis of the list of supposed Balticisms found by Czesław Kudzinowski (Acta Baltico-Slavica, I, Białystok, 1964, p. 223–225) in the environs of Knyszyn (the region of Białystok). The author of the article is of the opinion that an overwhelming majority of the words in Kudzinowski's list have entered the Polish dialects not from Yatvingian but from Lithuanian. Resp. an assumption is adopted that after the wars against the Teutonic Order this devastated land has been inhabited not only by Polish colonists from the West, by Belorussians and Ukrainians from the East and South-east, but also by Lithuanians from the North-east.
Keywords: baltų substratas Lenkijoje; baltizmai; leksikologija